Does the weekend matter? evaluating the weekend effect on pregnancy outcomes in first-cycle fresh IVF/ICSI embryo transfers: a retrospective study - Tianli Yang; Yuanyuan Yang; Zhaojuan Hou; Tianli Chang; Nenghui Liu; Donge Liu; Yumei Li; Jing Zhao; Qiong Zhang; Zhongyuan Yao; Fen Tian; Yanping Li (BMC Pregnancy and Childbirth)
Abstract Background The weekend effect is a controversial epidemiological phenomenon that has rarely been reported in the assisted reproductive technology (ART) setting, particularly among first-cycle fresh embryo transfer (ET) populations undergoing in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). Methods This was a retrospective cohort study including first fresh ET cycles in the Reproductive Medicine Center, Xiangya Hospital of Central South University from January 1, 2014 to March 1, 2022. Patients were divided into three groups based on the day of oocyte retrieval: Weekend Group, Near-Weekend Group and Midweek Group. Univariable and multivariate logistic regression analyses were performed to identify confounding factors and to evaluate associations between procedural timing and clinical pregnancy rate (CPR). Results A total of 8,200 first fresh ET cycles qualified for analysis after exclusions (16,121 screened), and were categorized based on the day of oocyte retrieval: Weekend Group (Saturday/Sunday, 27.06%, n = 2,219), Near-Weekend Group (Friday/Monday, 29.70%, n = 2,435), and Midweek Group (Tuesday/Wednesday/Thursday, 43.24%, n = 3,546). Oocyte retrievals near the weekend significantly reduced the odds of achieving CPR compared to midweek group (adjusted OR: 0.836, 95%CI: 0.728–0.960, p = 0.011). Weekend retrievals also showed lower odds of CPR, though not statistically significant (adjusted OR: 0.900, 95%CI: 0.781–1.037, p = 0.144). Compared to midweek oocyte retrievals, both the Weekend and Near-Weekend Groups demonstrated significantly lower live birth rates (46.73% vs. 43.88% vs. 43.49%, respectively; p = 0.023). Conclusions The timing of oocyte retrieval near weekends was associated with reduced CPR and live birth rate in fresh cycles. This study highlights the importance for maintaining consistent clinical vigilance—regardless of the day of the week—to optimize both pregnancy success rates and patient satisfaction.